Inference of individual ploidy level using codominant markers. (25th July 2019) - Huang, Kang; Dunn, Derek W.; Li, Zhonghu; Zhang, Pei; Dai, Yu; Li, Baoguo
Abstract: A significant portion of plant species are polyploids, with ploidy levels sometimes varying among individuals and/or populations. Current techniques to determine the individual ploidy, e.g., flow cytometry, chromosome counting or genotyping‐by‐sequencing, are often cumbersome. Based on the genotypic probabilities for polysomic inheritance under double‐reduction, we developed a model to estimate allele frequency and infer the ploidy status of individuals from the allelic phenotypes of codominant genetic markers. The allele frequencies are estimated by an expectation‐maximization algorithm in the presence of null alleles, false alleles, negative amplifications and self‐fertilization, and the posterior probabilities are used to assign individuals into different levels of ploidy. The accuracy of this method under different conditions is evaluated. Our methods are freely available in a new software package, ploidyinfer, for use by other researchers which can be downloaded from http://github.com/huangkang1987/ploidyinfer .